METHODOLOGY OF REGULATING AND DEVELOPING PRODUCTION AND ECONOMIC RELATIONS IN AGRICULTURE - Burkhanov Alisher Hadjimuradovich; Otabekov Javdod Nurilla O’g’li; Ayibov Daniyor Farkhod O’g’li (Scholar Express Journals, 2022)
In this article, the theoretical research of the nature and content of production and economic relations, scientific knowledge about production and economic relations, determining the decisive factors of their objective assessment and improvement, the methodology of regulating and developing relations in a multi-structural economy, its structure, methodology of approach, considering at the institutional level The need for exit, principles, requirements for methods in the short and long-term perspective to improve the efficiency of this industry and new economic relations are given based on recommendations
Keywords: Methodology; method; hypothesis; institutional